(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The Palst People are considered apart of the Hindu-European People Groups who left the areas North to the Mediteranian , near the Bilkan Peninsula, that is after They wewe strained by the diminishing food resources. The Plast People directed wagons pulled by bulls in order to attack the Kingdoms located east of the Mediteranian (such as the Levant , the Syrian coats , Egypt and Libya) . A great many researchers have tackled the issue of the origins of the Palestinians go back in history to the Palst people , a theory that explains the very name of Palestine.